Annulling an Annulled Annular Pancreas: A Case Report - Ghimire, Subodh; Dhakal, Sunil Kumar Sharma; Rai, Pranil; Rai, Nirvan; Mishra, Rajiv (Nepal Mediciti Medical Journal, 2023)
Annular Pancreas (AP) is a rare congenital developmental anomaly which results from failure of the ventral bud to rotate to fuse with the dorsal bud, resulting in a ring of pancreatic parenchyma that surrounds the second portion of the duodenum. This rare entity can be partial or complete and the partial is even rarer. Most cases manifest in the infancy but may remain asymptomatic and various nonspecific clinical manifestations are seen in adults. We report a rare case of partial annular pancreas with atrophy of body and tail of pancreas which presented with upper gastrointestinal bleeding and obstruction. The challenge in this case was the annular pancreas was the only functioning pancreatic tissue.